Lymph node dissection in lung cancer surgery - Patel, Akshay J.; Bille, Andrea (Frontiers in Surgery, 2024)
Lung cancer, a leading cause of cancer-related death, often requires surgical resection for early-stage cases, with recent data supporting less extensive resections for tumors smaller than 2cm. Central to resection is lymph node assessment, an area of controversy globally, compounded by advances in minimally invasive techniques. The review aims to assess current lymph node assessment standards, recent surgical era data, and the immunobiological basis of lymph node metastases' impact on patient outcomes. The British Thoracic Society guidelines recommend systematic nodal dissection during lung cancer resection, without specifying node removal or sampling. Historical data on mediastinal lymph node dissection (MLND) survival benefits are inconclusive, though proponents argue for lower recurrence rates. Recent trials like ACOSOG Z0030 found no survival difference between MLND and nodal sampling, reinforcing the need for robust staging. Lobe-specific dissection strategies have been proposed but lack consensus. JCOG1413 aims to compare lobe-specific and systematic dissection's clinical benefits. TNM-9 staging revisions emphasize single-station N2 involvement's prognostic significance. Robotic surgery shows promise, with trials like RAVAL reporting comparable outcomes to VATS and improved lymph node sampling. Immunobiological insights suggest preserving key immunological sites during lymphadenectomy, especially for patients receiving adjuvant immunotherapy. In conclusion, the standard lymph node resection strategy remains unsettled. The debate between systematic and selective dissection continues, with implications for staging accuracy and patient outcomes. As minimally invasive techniques evolve, robotic surgery may offer an effective and low-risk approach to delivering optimal lymph node assessment.